2011
DOI: 10.1002/jmri.22628
|View full text |Cite
|
Sign up to set email alerts
|

Nonenhanced extracranial carotid MR angiography using arterial spin labeling: Improved performance with pseudocontinuous tagging

Abstract: Purpose: To compare pulsed arterial spin labeling (PASL) and pseudocontinuous arterial spin labeling (PCASL) for nonenhanced extracranial carotid MR angiography (MRA). Materials and Methods:Parametric signal equations for PASL and PCASL MRA were formulated and compared. Volunteer imaging (n ¼ 7) at 1.5 Tesla was performed to compare the methods over a broad range of repetition and labeling times. Empirical results were compared with theoretical predictions. The feasibility of the optimal method was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Hybrid ASL (hASL) [187] is a new sequence that has been successfully applied to neurovascular MRA (Fig. 19) and is of crucial interest in pediatric subjects where non-contrastenhanced techniques must always be preferred.…”
Section: D Tse Sequence (Space)mentioning
confidence: 99%
“…Hybrid ASL (hASL) [187] is a new sequence that has been successfully applied to neurovascular MRA (Fig. 19) and is of crucial interest in pediatric subjects where non-contrastenhanced techniques must always be preferred.…”
Section: D Tse Sequence (Space)mentioning
confidence: 99%
“…A recently described nonsubtractive unenhanced MR angiographic technique called quiescent interval single shot shows minimal sensitivity to patient motion and cardiac arrhythmias and has been found to demonstrate peripheral arterial disease with accuracy comparable to that of contrastenhanced MR angiography (Fig 14) (151-153). Pseudocontinuous arterial spin-labeling techniques, which hitherto were primarily used for measurement of brain perfusion, have shown promise for unenhanced MR angiography of the head and neck (154,155).…”
Section: S193mentioning
confidence: 99%
“…Also, a previous study in 3D ASL-MRA has shown that substantially higher arterial signal was obtained by pCASL than PASL. 40 However, a dilemma shows up when using pCASL for dynamic MRA: because of its long labeling duration, the earliest labeled blood has already reached the distal arteries even for the first phase acquired immediately after the end of the labeling, thereby making it difficult to depict the early inflow phases ( Fig. 5b), which are easily depicted by PASL.…”
Section: Labeling Module (General)mentioning
confidence: 99%